Design and Synthesis of Acid‐resistant Zeolite T/NaY Composite Membrane for Water/Ethanol Separation. (30th May 2019) - Li, Xiangbo; Zhou, Zhihui; Chen, Liang; Kong, Chunlong; Du, Hongbin
Abstract : The random distribution of zeolite T on the porous α‐Al2 O3 tube during growth greatly limits its application in the industry. In this study, the defective zeolite T layer is modified with zeolite NaY. A continuous and dense zeolite T/NaY composite membrane is obtained through characterization by scanning electron microscope and X‐ray diffraction. The resulting composite membrane exhibits high selectivity and high permeation flux for 90 wt % ethanol/water solution at 75 °C. Water concentration in the permeation side of the as‐synthesized zeolite T/NaY composite membrane is >99.9 wt %, whereas that of primary zeolite T layer is only 60.4 wt %. The water permeation flux of the composite membrane reaches 4.35 kg/m 2 /h 1 . The composite membrane displays good stability in acid solution when the pH of the solution is >5. Abstract : The random distribution of zeolite T on the porous α‐Al2 O3 tube during growth greatly limits its application in the industry. In this study, the defective zeolite T layer is modified with zeolite NaY. A continuous and dense zeolite T/NaY composite membrane is obtained through characterization by scanning electron microscope and X‐ray diffraction. The resulting composite membrane exhibits high selectivity and high permeation flux for 90 wt % ethanol/water solution at 75 °C.